Sportszervezetek működési kereteinek változása - Bácsné Bába, Éva (Közép-Európai Közlemények, 2015)
Sports organizations are entities conventionally based on civil, non-governmental initiatives, and operating in non-profit legal forms. Concurrently with the strengthening business characteristics of sports, for-profit companies started to spread in increasing numbers. Currently, in Hungary sports organizations can be operated in the form of sports associations, business entities and public-benefit foundations for special purposes. The operating frameworks of sports organizations are currently defined in legal regulations. Business entities belong to the scope of the Act on Business Associations and other business-related legislation, whereas sports associations are subject to the Civil Act and the Civil Code. Obviously, the operation of sports organizations is also strongly influenced by the Sports Act. In consequence, it can be ascertained that the operation of sports organizations today is fairly strictly regulated. This publication has been written to describe the regulations relating to the organizations of the sports associations still constituting the majority of sports organizations, from the beginnings until the evolution of today’s system.